2018
DOI: 10.1177/2050312118788095
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of mental illness etiology and treatment in Saudi Arabian healthcare students: A cross-sectional study

Abstract: Objectives:Cultural beliefs often affect people’s attitude toward mental illness and their help-seeking behavior. Belief in superstitious causes of mental illness can lead to seeking help from non-medical practitioners, which might hinder treatment. This study aimed to explore the perception of mental illness and help-seeking behavior among healthcare students.Methods:A cross-sectional study carried out on a sample of 400 randomly selected undergraduate health professional students in Riyadh. Data collection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 33 publications
1
20
1
1
Order By: Relevance
“…A similar finding was noted in a qualitative study done in Saudi Arabia that found that mental illnesses among Muslims were perceived as possession by supernatural forces or punishment from God [ 27 ]. Moreover, stigma or shame of mental illness is not an uncommon finding among the Saudi community [ 2 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar finding was noted in a qualitative study done in Saudi Arabia that found that mental illnesses among Muslims were perceived as possession by supernatural forces or punishment from God [ 27 ]. Moreover, stigma or shame of mental illness is not an uncommon finding among the Saudi community [ 2 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…People diagnosed with mental illness are often rejected by the community and considered a burden to their families; thus, they, and their relatives, often hide the disorder from others because they fear public disapproval. Various studies have found that most people isolate themselves from individuals with mental illness, considering them dangerous and incapable of friendship [ 1 , 2 ]. Negative attitudes toward mental illness promote public discrimination against and stigmatization of patients with mental disorders and may cause them to withdraw from social interactions, which is likely to aggravate their mental illness condition [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies involved 16,391 participants who were primarily adults from the community. In six studies, participants were healthcare professionals [ 12 , 19 , 24 , 26 , 27 , 37 ], and five studies were conducted among college students [ 16 , 23 , 25 , 28 , 31 , 36 ]. In general, females constituted more than half of all study participants.…”
Section: Resultsmentioning
confidence: 99%
“…Fellmeth et al, 2015;Alahmed et al, 2018). Berbeda dengan penelitianPeltzer et al, (2016) menemukan bahwa penyedia yang sering berkonsultasi adalah dukun.…”
unclassified